2006
DOI: 10.1161/circulationaha.105.001081
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Injectable Collagen-Based Matrices for Improved Cell Delivery and Vascularization of Ischemic Tissue Using CD133 + Progenitors Expanded From the Peripheral Blood

Abstract: Background-The use of stem and/or progenitor cells to achieve potent vasculogenesis in humans has been hindered by low cell numbers, implant capacity, and survival. This study investigated the expansion of CD133 ϩ cells and the use of an injectable collagen-based tissue engineered matrix to support cell delivery and implantation within target ischemic tissue. Methods and Results-Adult human CD133ϩ progenitor cells from the peripheral blood were generated and expanded by successive removal and culture of CD133 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 24 publications
2
97
0
Order By: Relevance
“…In this regard, we have previously demonstrated by tracking cells with PET and by histology that our collagen-based matrix can improve cell retention and prevent excessive relocation of transplanted cells to nontarget tissues, 36 in addition to improving capillary density. 14 We also previously showed that CACs exposed to the matrix demonstrated higher levels of phosphorylated Akt (PI3K/Akt pathway) and increased survival under hypoxia. 15 Based on the ability of the collagen matrix to modulate the therapeutic phenotype and function of CACs, it may have induced similar effects in the pig model of this study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this regard, we have previously demonstrated by tracking cells with PET and by histology that our collagen-based matrix can improve cell retention and prevent excessive relocation of transplanted cells to nontarget tissues, 36 in addition to improving capillary density. 14 We also previously showed that CACs exposed to the matrix demonstrated higher levels of phosphorylated Akt (PI3K/Akt pathway) and increased survival under hypoxia. 15 Based on the ability of the collagen matrix to modulate the therapeutic phenotype and function of CACs, it may have induced similar effects in the pig model of this study.…”
Section: Discussionmentioning
confidence: 86%
“…14 In the present study, we induced and validated a preclinical model of myocardial ischemia and hibernation and used it to investigate the benefits of biopolymer-supported CAC delivery in this clinically relevant setting.…”
mentioning
confidence: 99%
“…Moreover, it is likely that a new appreciation for the mechanisms of action of current conventional pharmacological agents such as ACE inhibitors and statins will emerge with respect to matrix remodeling. In addition, it is becoming recognized that the structure and function of the interstitium play a critical role in the viability and phenotype of transplanted cells into the myocardium (212,430). Thus it is likely that improved understanding of myocardial matrix remodeling and degradation pathways will facilitate the development of pharmacological as well as cell-based treatment strategies for LV remodeling.…”
Section: The Myocardial Matrix As a Dynamic Entity Influencing Carmentioning
confidence: 99%
“…Microvascular wall thickness and lumen diameter were measured and their ratio calculated (18). In addition, capillary density was assessed in hematoxylin and eosin-stained sections under ϫ1,000 magnification as the ratio of capillaries to muscle fibers, as previously described (35,40).…”
Section: Methodsmentioning
confidence: 99%